E-cigarettes May Support Smokers With High Smoking-Related Risk Awareness to Stop Smoking in the Short Run: Preliminary Results by Randomized Controlled Trial. Issue 1 (11th April 2018) - Masiero, Marianna; Lucchiari, Claudio; Mazzocco, Ketti; Veronesi, Giulia; Maisonneuve, Patrick; Jemos, Costantino; Salè, Emanuela Omodeo; Spina, Stefania; Bertolotti, Raffaella; Pravettoni, Gabriella
Abstract: Introduction: E-cigarettes may be positively used in tobacco cessation treatments. However, neither the World Health Organization nor the American Food and Drug Administration has recognized them as effective cessation aids. Data about the efficacy and safety of e-cigarettes are still limited and controversial. Methods: This was a double-blind randomized controlled study. The main focus of this article is on a secondary outcome of the study, that is, the assessment of effectiveness and safety of e-cigarettes in achieving smoking cessation in a group of chronic smokers voluntarily involved in long-term lung cancer screening. Participants were randomized into three arms with a 1:1:1 ratio: e-cigarettes (Arm 1), placebo (Arm 2), and control (Arm 3). All subjects also received a low-intensity counseling. Results: Two hundred ten smokers were randomized (70 to nicotine e-cigarettes, 70 nicotine-free placebo e-cigarettes, and 70 to control groups). About 25% of participants who followed a cessation program based on the use of e-cigarettes (Arm 1 and Arm 2) were abstinent after 3 months. Conversely, only about 10% of smokers in Arm 3 stopped. A Kruskal-Wallis test showed significant differences in daily cigarettes smoking across the three arms (K-W = 6.277, p = .043). In particular, participants in Arm 1 reported a higher reduction rate (M = −11.6441, SD = 7.574) than participants in Arm 2 (M = −10.7636, SD = 8.156) and Arm 3 (M = −9.1379, SD = 8.8127). Conclusions: Our findings support the efficacy and safety of e-cigarettes in a short-term period. E-cigarettes use led to a higher cessation rate. Furthermore, although all participants reported a significant reduction of daily cigarette consumption compared to the baseline, the use of e-cigarettes (including those without nicotine) allowed smokers to achieve better results. Implications: E-cigarettes increased the stopping rate as well as the reduction of daily cigarettes in participants who continued smoking. In fact, although all participants reported a significant reduction of tobacco consumption compared to the baseline, the use of e-cigarettes allowed smokers to achieve a better result. It could be worthwhile to associate this device with new ICT-driven models of self-management support in order to enable people to better handle behavioral changes and side effects. This is true for ready-to-quit smokers (such as our participants) but can also be advantageous for less motivated smokers engaged in clinical settings.